2021
DOI: 10.1093/bib/bbaa400
|View full text |Cite
|
Sign up to set email alerts
|

iCysMod: an integrative database for protein cysteine modifications in eukaryotes

Abstract: As important post-translational modifications, protein cysteine modifications (PCMs) occurring at cysteine thiol group play critical roles in the regulation of various biological processes in eukaryotes. Due to the rapid advancement of high-throughput proteomics technologies, a large number of PCM events have been identified but remain to be curated. Thus, an integrated resource of eukaryotic PCMs will be useful for the research community. In this work, we developed an integrative database for protein cysteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 61 publications
4
16
0
Order By: Relevance
“…Cys residues in Hsp70 generally show modest reactivity in global profiling of the cysteinome [ 55 ]. Over the past twenty years development of methods for enrichment of Cys-modified proteins and mass spectrometry (MS) detection has allowed extensive identification of cysteine modifications in Hsp70 members ( Table S1 ), which have been summarized in databases for protein cysteine modifications [ 56 , 57 , 58 , 59 , 60 ]. Once cysteine modifications have been identified, the next goal is to identify the effects of cysteine modifications on the structure and function of Hsp70 and the physiological significance of these changes.…”
Section: Post-translational Modifications Of Hsp70 Under Oxidative St...mentioning
confidence: 99%
“…Cys residues in Hsp70 generally show modest reactivity in global profiling of the cysteinome [ 55 ]. Over the past twenty years development of methods for enrichment of Cys-modified proteins and mass spectrometry (MS) detection has allowed extensive identification of cysteine modifications in Hsp70 members ( Table S1 ), which have been summarized in databases for protein cysteine modifications [ 56 , 57 , 58 , 59 , 60 ]. Once cysteine modifications have been identified, the next goal is to identify the effects of cysteine modifications on the structure and function of Hsp70 and the physiological significance of these changes.…”
Section: Post-translational Modifications Of Hsp70 Under Oxidative St...mentioning
confidence: 99%
“…Previously, numerous informative databases have been constructed to store PTM-related data in plants. For example, some general resources, such as dbPTM ( 25 ) and SysPTM ( 26 ), contain various types of PTMs identified by experiments in eukaryotes, while several PTM-specific databases, including EPSD ( 27 ), PLMD ( 28 ) and iCysMod ( 29 ), host modified sites for phosphorylation, lysine modifications and cysteine modifications in eukaryotic proteins, respectively. However, these databases only cover a limited part of the experimentally identified PTM events in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike external H2O2 addition, peroxisomal H2O2 production did not result in a po-IBD-SBP-YAP1C-mediated trapping of ACOX1 or MDH1. Nonetheless, such treatment did result in the trapping of various cytosolic, cytoskeletal, and plasma membrane-associated proteins (Table S4), many of which are known to be sulfenylated on at least one cysteine residue [Wang et al, 2021]. Importantly, given that (i) we have previously demonstrated that peroxisomederived H2O2 can efficiently permeate across the peroxisomal membrane [Lismont et al, 2019a], (ii) a small portion of po-IBD-SBP-YAP1C is mislocalized to the cytosol (Fig.…”
Section: The Cytosolic Mitochondrial and Peroxisomal Sulfenome Undergo Time-dependent Changes Upon Peroxisomal H2o2 Generationmentioning
confidence: 95%